Artery-on-a-chip platform for automated, multimodal assessment of cerebral blood vessel structure and function1. Issue 12 (21st June 2015) - Yasotharan, Sanjesh; Pinto, Sascha; Sled, John G.; Bolz, Steffen-Sebastian; Günther, Axel
<x xml:space="preserve">Abstract</x> We present a compact microfluidic platform for the automated, multimodal assessment of intact small blood vessels in vitro.